Microplastics in Lake Poso Sediments and Their Use as Educational Media - Agreista Toripa; Fatmah Dhafir; Musdalifah Nurdin; Masrianih; Abd. Hakim Langgeng; Syech Zainal (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2026)
Microplastic pollution is an emerging environmental concern because these particles can accumulate in aquatic ecosystems but are difficult to detect visually. This study aimed to identify the morphological types and determine the density of microplastics in sediments from Lake Poso, Central Sulawesi, Indonesia, and to develop an educational poster based on the findings. A quantitative descriptive approach was applied. Sediment samples were collected from three categories of sites: an area with minimal human activity, a tourism area, and a residential area. Two sampling points were established at each site, yielding six sediment samples. At each sampling point, 200 mL of sediment was collected using the hand-collection method and analyzed at the Biology Laboratory, Faculty of Teacher Training and Education, Tadulako University. Organic matter was digested using a 10% KOH solution, after which the samples were filtered and examined microscopically. Suspected microplastic particles were classified as fibers, fragments, films, or pellets. Microplastics were detected in all sediment samples, although their density varied among sites. Fragments were the most abundant type, followed by fibers, films, and pellets. Microplastic densities were 170 particles/100 g of dry sediment at the site with minimal human activity, 281 particles/100 g at the tourism site, and 218.5 particles/100 g at the residential site. The educational poster developed from these findings was evaluated by content, design, and media experts, as well as student users, and was categorized as highly suitable for educational use. These findings indicate that Lake Poso sediments are contaminated with microplastics, potentially associated with tourism, fisheries, residential activities, and other anthropogenic inputs. Improved waste management and environmental monitoring are therefore needed to reduce microplastic contamination in the lake.